PENGARUH TATA RUANG DAN KOMUNIKASI INTERN TERHADAP EFEKTIVITAS KERJA GURU DI SMK NEGERI 9 SEMARANG - Rustiana, Ade; Rosmawati, Nela Harni (Fakultas Ekonomi, Universitas Negeri Semarang, 2010)
Office layout is a method to formulate spatial, tools, layout, and their physical environment that aims to provide a means for teachers and internal communications are an important means to unify the direction and the views and thoughts among teachers and between teachers with the Head of School, so create cohesion in the work. This research aims: 1) to determine whether there is any spatial effect on the effectiveness of teachers 'work; 2) to determine whether there is an internal communication influence the effectiveness of teachers' work; 3) to know how big influence of spatial planning and internal communication on the effectiveness of working collectively same. The population that became the subject of this study was the teacher of SMK Negeri 9 Semarang all 44 people who made the research sample because this study represents a population study. In this study, the independent variables are spatial and internal communications, while the dependent variable is the employment effectiveness of teachers. Data collection was performed using a questionnaire technique, documentation and observation. Data analysis technique used is descriptive analysis percentages, multiple regression analysis, simultaneous test, partial test, coefficient of determination and classical assumption. Based on the results of regression analysis obtained F value of 13.357 with a probability of 0.000 <0.05, which means that there is significant influence between spatial planning and internal communication on the effectiveness of teacher working SMK Negeri 9 Semarang. The amount of influence between spatial planning and internal communication on the effectiveness of teacher working SMK Negeri 9 for 39.5% of Semarang. Based on this research, the authors suggest that: in drafting desk should be more loose and in placing the furniture and other equipment should be to take advantage of the space available, so the staff room and classrooms and teachers more impressed with a neat move freely when doing academic activities; head schools should pay more attention to another teacher performance by giving instructions clearly did not even hesitate to reprimand if proven negligent in completing the job, as an effort to improve the quality of education, school principals should be willing to open ourselves to receive all complaints, ideas, or ideas from teachers.